(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
When it comes to protecting the body from harmful substances, the immune system is firstline of defence. Lymph nodes, tonsils, adenoids, and the thymus are only few of the organs and tissuesthat make up the human immune system. Germs need to get past the body’s natural defences, suchmucus and enzymes, before they can infect a host. In order to begin destroying healthy cells, they mustfirst overcome these barriers. If a pathogen is able to get past the first layer of defence, it will be sent tothe next level of protection. There are two main types of immune system responses to infections innateand adaptive. Host innate or nonspecific immune cells like macrophages and dendritic cells areresponsible for the early response to infections. Specific immunity, or acquired immunity, is establishedby the body’s manufacture of antibodies that are highly specific to the antigens that caused an infection.Both naturally occurring chalcones and synthetically synthesised chalcones, together with theirrespective derivatives, have been shown to possess intrinsic anticancer and anti-inflammatory effects.Clinical trials are currently the only reliable means of gauging a treatment’s potential therapeutic benefit.In order to create more effective molecules, it would be helpful to have access to compounds with welldefinedmechanisms of action. In this research, we synthesised a boronic Chalcone derivative andanalysed its immunomodulatory effects.